Understanding Zakat as a Form of Women's Empowerment Through the Role of Fatayat NU in Jember Regency - Qur'ani, Gilang Lita; Indrianti, Deditiani Tri; Ariefianto, Lutfi (Universitas Pendidikan Indonesia (UPI), 2023)
Understanding zakat in Islam is very important for everyone, especiallywomen. Where women have a vital role in the family, both as companionsto their husbands and also as educators for their future children. Literacyand a good understanding of zakat is one factormuzakkiin making thedecision to pay zakat, whether zakat fitrah or zakat maal. Apart from that,understanding zakat is also a symbol of empowerment because zakat is adistribution of assets that can create prosperity and overcome poverty.Determining the location in this research uses techniquespurposive areanamely at the NU Fatayat Organization at the Jember Regency BranchLevel. The technique for determining informants in this research usestechniquespurposive sampling, then techniques for obtaining data frominformants use techniquessnowball sampling. Data collection techniqueswere carried out using observation, interviews and documentationtechniques. Data validity checking techniques use extended participation,increased persistence, and triangulation. Data analysis was carried out byprior analysis in the field and analysis in the field. The research resultsillustrate that Fatayat women have understood the concept of zakat ingeneral from their own perspective in terms of aspectsmuzakki,mustahiqand institutional aspects. However, it is still felt that theunderstanding of zakat maal needs to be further disseminated to thecommunity. The Fatayat NU organization plays a role in providing access,awareness and participation regarding zakat to women. With theexistence of economic, social and da'wah structures, there is greatpotential if education and understanding of zakat is used as anempowerment program. So that in the end it can create a zakat literatesociety.